2019
DOI: 10.17973/mmsj.2019_11_2019056
|View full text |Cite
|
Sign up to set email alerts
|

Free-Form Tools Design and Fabrication for Flank Super Abrasive Machining (Fsam) Non Developable Surfaces

Abstract: Manufacturing improvements are becoming a real need in industry. In order to satisfy these industrial requirements, they should be targeted in two different directions: new manufacturing processes and surface optimization through algorithms. On the one hand, Super Abrasive Machining (SAM) is presented as a new manufacturing process combining benefits from milling and grinding technologies. On the other hand, there is a tendency to manufacture non developable surfaces by flank milling and to achieve final dimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…The developed algorithm ensures that the resultant envelope is a highly accurate approximation of the input free-form surface. Furthermore, similar approach was applied to create a Super Abrasive Machining (SAM) tool considering a blade surface generatrix [18], where it is shown that this new technology of custom-shaped tools is advantageous both in terms of accuracy and manufacturing time.…”
Section: Figure 1 a Bi-cubic Bézier Patch With Its Control Network Co...mentioning
confidence: 99%
“…The developed algorithm ensures that the resultant envelope is a highly accurate approximation of the input free-form surface. Furthermore, similar approach was applied to create a Super Abrasive Machining (SAM) tool considering a blade surface generatrix [18], where it is shown that this new technology of custom-shaped tools is advantageous both in terms of accuracy and manufacturing time.…”
Section: Figure 1 a Bi-cubic Bézier Patch With Its Control Network Co...mentioning
confidence: 99%